The accidental empress : a novel - Pataki, Allison (Howard Books, a division of Simon & Schuster, Inc., 2015)
The New York Times best-selling author of The Traitor's Wife fictionalizes the little-known and tumultuous love story of "Sisi," the 19th-century Austro-Hungarian empress and captivating wife of Emperor Franz Joseph.